Three new andrastin derivatives from the endophytic fungus Penicillium vulpinum - Yu-Yue Qin; Xi-Shan Huang; Xiao-Bo Liu; Tu-Xiang Mo; Zhao-Long Xu; Ben-Chao Li; Xiao-Ya Qin; Jun Li; Till F. Schӓberle; Rui-Yun Yang (Natural Product Research, 2020)

Production of functional human nerve growth factor from the submandibular glands of mice using a CRISPR/Cas9 genome editing system - Yi Gu; Hui Cao; Fei Li; Jianli Yu; Rui Nian; Dongxiao Feng; Jingtao Lin; Haipeng Song; Wenshuai Liu (World Journal of Microbiology and Biotechnology, 2020)

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

Fundamental Characteristics of Tropical Rain Cell Structures as Measured by TRMM PR - Yunfei Fu; Yilun Chen; Xiangdong Zhang; Yu Wang; Rui Li; Qi Liu; Lei Zhong; Qiong Zhang; Aoqi Zhang (Journal of Meteorological Research, 2020)

Sphingobacterium endophyticum sp. nov., a novel endophyte isolated from halophyte - Yang-Yang Liu; Fang Liu; Yu-Qian Li; Rui-Feng Lei; Qin Ma; Manik Prabhu Narsing Rao; Dilireba Abudourousuli; Zulihumaer Rouzi; Muyesaier Aosiman; Deng-Di An; Wen-Jun Li (Archives of Microbiology, 2020)

Energy conservation and carbon reduction potential for solid waste in China - Minxi Wang; Zhi Li; Lu Chen; Ping Liu; Rui Zhang; Wei Liu; Yu Ma; Yajie Wang; Xin Li (Environmental Science and Pollution Research, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Two new anthraquinone derivatives and one new triarylbenzophenone analog from Selaginella tamariscina - Rui Liu; Hui Zou; Zhen-Xing Zou; Fei Cheng; Xia Yu; Ping-Sheng Xu; Xiao-Min Li; Dai Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

Sulfur isotope and trace element compositions of pyrite determined by NanoSIMS and LA-ICP-MS: new constraints on the genesis of the Shuiyindong Carlin-like gold deposit in SW China - Jin-xiang Li; Rui-zhong Hu; Cheng-hai Zhao; Jing-jing Zhu; Yong Huang; Wei Gao; Jin-wei Li; Yu-zhou Zhuo (Mineralium Deposita, 2020)

Psychroflexus maritimus sp. nov., isolated from coastal sediment - Yan-Lin Zhong; Rui Zhang; Xiao-Yu Zhang; Li-Xue Yu; Meng-Fan Zhao; Zong-Jun Du (Archives of Microbiology, 2020)

Electroacupuncture improves myocardial ischemia injury via activation of adenosine receptors - Yulan Ren; Zhihan Chen; Rui Wang; Yang Yu; Dehua Li; Yonggang He (Purinergic Signalling, 2020)
Electroacupuncture (EA) can improve myocardial ischemia (MI) injury; nevertheless, the mechanism is not entirely clear. And there were disagreements about whether the effect of EA at acupoint in disease-affected meridian is better than EA at acupoint in non-affected meridian and sham acupoint. Here, we showed that the effect of EA at Neiguan (PC6) is better than EA at Hegu (LI4) and sham acupoint in affecting RPP and ECG, increasing ATP and ADO production, decreasing AMP production, and upregulating the mRNA expression levels of A1AR, A2aAR, and A2bAR; knockdown of A1AR or A2bAR reversed the effect of EA at PC6 in alleviating MI injury; knockdown of A2aAR had no influence on the cardiac protection of EA at PC6; thus, the cardioprotective effect of EA at PC6 needs A1AR and A2bAR, instead of A2aAR; considering that the cardio protection of adenosine receptor needs activation of other adenosine receptors, one of the reasons may be that after silence of A1AR or A2bAR, EA at PC6 could not impact the expression levels of the other two adenosine receptors, and after silence of A2aAR, EA at PC6 could impact the expression levels of A1AR and A2bAR. These results suggested that EA at PC6 may be a potential and effective treatment for MI by activation of A1AR and A2bAR.

The abscisic acid receptor gene VvPYL4 positively regulates grapevine resistance to Plasmopara viticola - Li Liu; Chang-Yuan Liu; Hui Wang; Shu-Yi Yu; Tian-Shu Guan; Yu-Fei Huang; Rui-Chun Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Alleviation of Cd phytotoxicity and enhancement of rape seedling growth by plant growth–promoting bacterium Enterobacter sp. Zm-123 - Meng Zhang; Zonghui Jin; Xu Zhang; Guoliang Wang; Rui Li; Juanjuan Qu; Yu Jin (Environmental Science and Pollution Research, 2020)

Reconstructing the 3D digital core with a fully convolutional neural network - Qiong Li; Zheng Chen; Jian-Jun He; Si-Yu Hao; Rui Wang; Hao-Tao Yang; Hua-Jun Sun (Applied Geophysics, 2020)

A new phenanthropyran and a new biphenanthrene from the rhizomes of Dioscorea septemloba and their antioxidant activities - Tao He; Yi Liu; Rui-Feng Xiong; Xiao-Yu Li; Shou-Feng Wang; Chun-Ru Cheng (Natural Product Research, 2020)

Ablation of olfactory bulb glutamatergic neurons induces depressive-like behaviors and sleep disturbances in mice - Mao-Yun Yuan; Ze-Ka Chen; Jian Ni; Tian-Xiao Wang; Shi-Yu Jiang; Hui Dong; Wei-Min Qu; Zhi-Li Huang; Rui-Xi Li (Psychopharmacology, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Effects of crop straw biochars on aluminum species in soil solution as related with the growth and yield of canola (Brassica napus L.) in an acidic Ultisol under field condition - Wen-rui Zhao; Jiu-yu Li; Kai-ying Deng; Ren-yong Shi; Jun Jiang; Zhi-neng Hong; Wei Qian; Xian He; Ren-kou Xu (Environmental Science and Pollution Research, 2020)

Pseudomonas Saliphila sp. nov., a Bacterium Isolated from Oil-Well Production Water in Qinghai Oilfield of China - Xiao-Juan Zhang; Hong-Can Liu; Yu-Guang Zhou; Xiao-Lei Wu; Yong Nie; Qi-Rui Li; Mei-Zhu Wang; Liang Zhao; Man Cai; Ying-Qian Kang (Current Microbiology, 2020)

Correlation Between CCG Polymorphisms and CAG Repeats During Germline Transmission in Chinese Patients with Huntington’s Disease - Hong-Rong Cheng; Xiao-Yan Li; Hui-Li Yu; Miao Xu; Yan-Bin Zhang; Shi-Rui Gan; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2020)

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

The characteristic of the synonymous codon usage and phylogenetic analysis of hepatitis B virus - Xiaoming Qi; Chaojun Wei; Yonghong Li; Yu Wu; Hui Xu; Rui Guo; Yanjuan Jia; Zhenhao Li; Zhenhong Wei; Wanxia Wang; Jing Jia; Yuanting Li; et al. (Genes & Genomics, 2020)
Background Hepatitis B virus (HBV) infection is a crucial medical issue worldwide. The dependence of HBV replication on host cell machineries and their co-evolutionary interactions prompt the codon usage pattern of viral genes to translation selection and mutation pressure. Objective The evolutionary characteristics of HBV and the natural selection effects of the human genome on the codon usage characteristics were analyzed to provide a basis for medication development for HBV infection. Methods The codon usage pattern of sequences from different HBV genotypes of our isolates and reference HBV genome sequences downloaded from the National Center for Biotechnology Information (NCBI) database were analyzed by computing the relative synonymous codon usage (RSCU), nucleotide content, codon adaptation index (CAI) and the effective number of codons (ENC). Results The highest ENC values were observed in the C genotypes, followed by the B genotypes. The ENC values indicated a weak codon usage bias (CUB) in HBV genome. The number of codons differentially used between the three genotypes was markedly higher than that of similarly used codons. High CAI values indicated a good adaptability of HBV to its host. The ENC plot indicated the occurrence of mutational pressure in the three genotypes. The mean Ka/Ks ratios in the three genotypes were lower than 1, which indicated a negative selection pressure. The CAI and GC3% plot indicated the existence of CUB in the HBV genome. Conclusions Nucleotide composition, mutation bias, negative selection and mutational pressure are key factors influencing the CUB and phylogenetic diversity in HBV genotypes. The data provided here could be useful for developing drugs for HBV infection.

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Empathic Contagious Pain and Consolation in Laboratory Rodents: Species and Sex Comparisons - Rui Du; Wen-Jun Luo; Kai-Wen Geng; Chun-Li Li; Yang Yu; Na Wei; Jun Chen (Neuroscience Bulletin, 2020)

Synthesis, pharmacological evaluation and molecular docking of novel R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid as dual anti-inflammatory anti-platelet aggregation agents - Rong Rong; Rui-zhen Zhang; Xin Wang; Yu-han Dan; Yun-li Zhao; Zhi-guo Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Characterization of a Rapeseed Anthocyanin-More Mutant with Enhanced Resistance to Sclerotinia sclerotiorum - Rui Liu; Li-Na Ding; Ming Li; Wei Cao; Yu-Kang Wang; Wei-Jie Wang; Yan-Kun Yu; Zheng Wang; Ke-Ming Zhu; Xiao-Li Tan (Journal of Plant Growth Regulation, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Spent mushroom substrate combined with alkaline amendment passivates cadmium and improves soil property - Zonghui Jin; Meng Zhang; Rui Li; Xu Zhang; Guoliang Wang; Xuesheng Liu; Juanjuan Qu; Yu Jin (Environmental Science and Pollution Research, 2020)

Development of 19 novel microsatellite markers of lily-of-the-valley (Convallaria, Asparagaceae) from transcriptome sequencing - Qi-Xiang Lu; Jing Gao; Jun-Jie Wu; Xuan Zhou; Xue Wu; Meng-Di Li; Yu-Kun Wei; Rui-Hong Wang; Zhe-Chen Qi; Pan Li (Molecular Biology Reports, 2020)

Characteristics, Sources, and Risks of Polycyclic Aromatic Hydrocarbons in Topsoil and Surface Water from the Liuxi River Basin, South China - Zhenglan Xie; Lei Gao; Zuobing Liang; Jianyao Chen; Shaoheng Li; Aiping Zhu; Yu Wu; Zhigang Yang; Rui Li; Zhuowei Wang (Archives of Environmental Contamination and Toxicology, 2020)

Molecular cloning and functional characterization of the CEP RECEPTOR 1 gene MdCEPR1 of Apple (Malus × domestica) - Rui Li; Jian-Ping An; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

The giant Zaozigou Au-Sb deposit in West Qinling, China: magmatic- or metamorphic-hydrothermal origin? - Kun-Feng Qiu; Hao-Cheng Yu; Jun Deng; Duncan McIntire; Zong-Yang Gou; Jian-Zhen Geng; Zhao-Shan Chang; Rui Zhu; Kang-Ning Li; Richard Goldfarb (Mineralium Deposita, 2020)

Interaction between CA repeat microsatellites and HIF1α regulated the transcriptional activity of porcine IGF1 promoter - Hongwei Geng; Linlin Hao; Yunyun Cheng; Chunli Wang; Shan Huang; Wenzhen Wei; Rui Yang; Haoyang Li; Songcai Liu; Hao Yu; Huayi Lu (Journal of Applied Genetics, 2020)

Crystal structure of impurity-free rhodochrosite (MnCO3) and thermal expansion properties - Wen Liang; Lin Li; Rui Li; Yuan Yin; Zeming Li; Xiqiang Liu; Shuangmin Shan; Yu He; Yong Meng; Zengsheng Li; Heping Li (Physics and Chemistry of Minerals, 2020)

Anfibatide Preserves Blood–Brain Barrier Integrity by Inhibiting TLR4/RhoA/ROCK Pathway After Cerebral Ischemia/Reperfusion Injury in Rat - Peng Gong; Rui Li; Hui-Yu Jia; Zheng Ma; Xiao-Yi Li; Xiang-rong Dai; Sheng-Yong Luo (Journal of Molecular Neuroscience, 2020)

Hirsutella sinensis inhibits NLRP3 inflammasome activation to block aristolochic acid-induced renal tubular epithelial cell transdifferentiation - Min Yu; Yu-lin Man; Meng-hua Chen; Li-hua Wu; Yi Zhou; Xiao-ling Zhou; Na Chen; Rui Ma; Li-na Sun (Human Cell, 2020)

Systematic analysis of lncRNA expression profiles and atherosclerosis-associated lncRNA-mRNA network revealing functional lncRNAs in carotid atherosclerotic rabbit models - Yingnan Wu; Feng Zhang; Xiaoying Li; Wenying Hou; Shuang Zhang; Yanan Feng; Rui Lu; Yu Ding; Litao Sun (Functional & Integrative Genomics, 2020)

Uptake and accumulation of pentachloronitrobenzene in pak choi and the human health risk - Ming Li; Guanghui Xu; Rui Yu; Yang Wang; Yong Yu (Environmental Geochemistry and Health, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)